Isolation, Identification and Molecular Characterization of Highly Pathogenic Newcastle Disease Virus From Field Outbreaks - Ashraf,Asma (2016)
ABSTRACT Newcastle disease (ND) is a major infectious disease of the poultry caused by a virulent strain of Avian Paramyxovirus - 1, that is a single strand non-segmented negative sense RNA virus. ND virus is major threat to the poultry industry in many countries of the world. The study was aimed to isolate and identify Newcastle disease virus (NDV) by using a haemagglutination inhibition (HI) test and reverse transcription-polymerase chain reaction (RT-PCR) assay. A total 100 samples of infected and dead birds were collected from different poultry farms. The weight of the birds was ranged 1000-1200g. The birds were divided into 3 groups. Haemagglutination assay (HA) was performed to detect the presence of NDV in suspension of infected homogenized tissues and it was found that HA is not the best method to detect the virus when it is in trace amounts. RT-PCR using NDV specific primers analyzed different clinical and postmortem samples. Reverse transcriptase polymerase chain reaction and specific primers was used for determining the presence of viruses. It was found that the virus was present in most of the infected samples except the serum of infected birds. During multiple sequence alignment (MSA) it was found that, our isolates have high homology (98%) with other reported NDV isolates. Phylogenetic analysis revealed that our isolate was closely related with viscerotropic velogenic types of NDV, which are highly pathogenic Newcastle disease virus.